Preparation and Properties of Epoxy Composites with Multi-Scale BN Sheets - Sijiao Wang; Kaiming Cao; Guanwei Wang; Mengmeng Chen; Hongxi Wang (Applied Sciences, 2022)
Epoxy resin is one of the most widely used thermosetting polymers and commonly applied in power electronics field. The intrinsic properties of epoxy can be improved by the introduction of inorganic filler, thus fabricating a composite material. In this paper, different scales of modified boron nitride (BN, 1 μm, 10 μm) were used to improve the thermal conductivity of epoxy resin. The surfaces BN were modification by a silane coupling agent to improve the compatibility between BN and epoxy resin. The effects of micro-and nano-BN sheets on the microstructure, breakdown strength, thermal and mechanical properties of epoxy resin composite were studied. The characterization of its morphology by scanning electron microscopy shows that nano-BN distribution is in the middle of micro-BN, forming a better bridging effect. The data of the breakdown strength and thermal conductivity indicated that when the content of micro-BN is 30 wt% and nano-BN is 20 wt%, the thermal conductivity of BN/epoxy composite was 1.52 W/m·K. In addition, the breakdown strength is 77.1 kV/mm. Thus, this type of BN-filled BN/EP composites with remarkable insulation and thermal conductivity properties would have potential for power engineering materials.